MERCHMENOT: APPLYING MERCHANDISING CONCEPTS WITH ACTIVE LEARNING. Issue 2 (3rd April 2021) - VanMeter, Rebecca A.; Vander Schee, Brian A.
ABSTRACT: Active learning engages students where they enjoy the learning process and gain a better understanding of course content. Active learning, such as an in-class game, can mitigate inattentive listening to material presented in a traditional lecture format. The Merch Game is an innovative, in-class retail simulation game that uses student collaboration and competition with a focus on merchandising concepts. The goal of the innovation is to raise awareness regarding concepts related to merchandising in the game. The innovation is outlined, and student written reflections provide the data to employ quantitative content analysis. Results demonstrate the in-class game met its learning objectives, namely, recognition, comprehension, and application of merchandising concepts. Application to other settings and future research opportunities are also discussed.